Simple life: an inquiry into the joys of simplicity in a complex world - Jayakumar, K. (Gurugram Shubhi, 2021)
This book is an inquiry into simplicity. However, simplicity has complex connotations. It does not necessarily mean renunciation of all comforts and enjoyment. It is not a life of deprivation or enforced poverty. It is not an ascetic life. Evidently simplicity has complexity as its antonym. This book is based on the premise that modern life is complex and it triggers more attendant complexities. It is an attempt to explore the countervailing conscious strategies to resist the onslaught of complexity. Life in the twenty first century is characterized by external and internal complexity of all kinds; financial, emotional, and behavioural, all of them cumulatively stealing simplicity out of our lives. The deeper tragedy is that the ideological architecture that rules the world today is designed not to make life simpler but to perpetuate complexity. This is accomplished by releasing the powerful forces of extravagant and avoidable consumption. Global capitalism which is the dominant ideology of the day has its intricate network that allures the world to the consumerist paradise. Consumption becomes an addiction, seeking (the elusive) satisfaction and (the unattainable) contentment; It is driven by the inner longing to find meaning for life. Global capitalism has to necessarily resist and discredit simplicity. While being aware of the might of this global economic behemoth, this book tries to pose the question whether an alternative lifestyle is possible. The inquiry affirms that it is not only possible but it is a moral imperative to prevent the threatening ecological calamity which has its roots solely in the lifestyle legitimized by consumption-led growth. Market is the deity of our times. The pressing need to revive the economies shattered by the Second World War and the development compulsions of the newly independent nations of the mid 20th century brought industrial production and commerce to centre stage.
Keywords: Simplicity